Pelatihan Pembuatan Bak Terpal - Abidin, Zaenal; Amir, Sadikin; Damayanti, Ayu Adhita; Mukhlis, Alis (Dewan Pimpinan Daerah (DPD) Forum Dosen Indonesia JATIM, 2017)
The activity aimed to train a targeted group in making fish tank tarpaulin which had a diameter of 150 cm, andhigh of 125 cm. Methode which was used in this project were making focus group discussion and practicing directly inmaking tarpaulin tank. Each person in the group was involved actively in all session, start from tools and materialspreparation, cutting material, frame construction, shaping the tarpaulin, till tank assembly. Through these activity, thegroup was succes to build 1 unit tank tarpaulin which was ready to use for aquaculture activity